Ammonia-oxidizing archaea and ammonia-oxidizing bacteria communities respond differently in oxy-gen-limited habitats - Du, Jialin; Meng, Lin; Qiu, Mingsheng; Chen, Shuaiwei; Zhang, Binghui; Song, Wenjing; Cong, Ping; Zheng, Xuebo (Frontiers in Environmental Science, 2022)
Ammonia-oxidizing archaea (AOA) and bacteria (AOB) are the most important ammonia oxidation func-tional community, while the coastal environment just provides a different oxygen environment for the am-monia oxidation process. However, few surveys concentrated on the influence of oxygen concentration on the niche specialization of AOA and AOB in the ocean intertidal zones. Here, high-throughput sequencing by Illumina MiSeq and qPCR were applied to detect the change of abundance, diversity as well as communi-ty structure of both AOA and AOB with 0-60 cm sediments depth in the intertidal zone in Qingdao, China. Results showed that the AOA/AOB amoA gene copy numbers and AOA/AOB OTU numbers rate increased as sediment depth went more profound, which indicated that AOA was more adaptive to oxygen-limited niches compared to AOB. Oxygen indeed led to the niche specialization of AOA and AOB in intertidal sed-iments. The dominant AOA and AOB were the clusters of Nitrosopumilus and Nitrosospira, respectively, which indicated ecological success in the intertidal zone. A significant and positive correlation (P< 0.01) be-tween AOB abundance/AOB OTU numbers and Oxidation-reduction potential (ORP) was observed. In ad-dition, both total nitrogen (TN) (P< 0.01) and pH (P< 0.05) were significantly negatively correlated to AOB abundance. TN was also significantly negatively correlated to AOB OTU numbers (P< 0.05). Hence, oxygen led to niche specialization of AOA and AOB, especially under anoxic conditions, AOA played a dominant role in the process of ammonia oxidation. The Nitrosopumilus and Nitrosospira clusters were the dominant AOA and AOB, respectively, representing an ecological success in the intertidal zone.